Home-based high-intensity interval training can improve physical performance in young female athletes during a quarantine - Müller, Camila Borges; da Veiga, Rousseau Silva; dos Santos Pinheiro, Eraldo; Del Vecchio, Fabrício Boscolo; Zanesco, Angelina [UNESP] (My University, 2022)
Aim: To verify the effects of a 2-week of high-intensity interval training (HIIT) on physical performance in young female athletes. Methods: female rugby players (n = 13; 15.92 ± 0.76 years old) participated in an 8-session of HIIT supervised through online video calls for two weeks. They were evaluated pre- and post-HIIT for 3-min of burpees, 1-min of sit-ups, maximum push-ups, and 1-min of squats. Perceptions related to training protocols were collected through the Physical Activity Enjoyment Scale (PACES) post-intervention. Results: Significant improvements in burpees (pre:54.15 ± 18.03 and after: 63.15 ± 15.18), sit-ups (pre:24.38 ± 13.38 and after: 31.15 ± 13.15), push-ups (pre: 9.46 ± 6.59 and after: 13.85 ± 7.33) and squats (pre: 48.00 ± 8.37 and after: 54.85 ± 8.79) were observed. PACES revealed positive perceptions related to the enjoyment of participating in this HIIT. Conclusion: Virtually supervised HIIT improved physical performance in young female athletes during the COVID-19 pandemic, and maybe an efficient strategy for the quarantine period.
Keywords: Adolescent; Athletes; High-intensity interval training; Internet-based intervention; Women